Envelhecimento saudável e promoção da saúde: reflexão dos idosos acerca da qualidade de vida - Sousa, Ana Cândida Pinto de (2022)
This work highlights the importance of the perception of the Quality of Life of the elderly in the search for healthy aging. Brazil has experienced an accelerated population aging process, which is a global reality and a major challenge. Healthy and active aging allows people to realize their potential for physical, social and mental well-being throughout the course of life, and for these people to participate in society according to their needs, desires and capabilities; at the same time, it provides protection, security and proper care when needed. With this, it increases the expectation of a healthy life and the quality of life for all people who are aging, including those who are frail, physically disabled and who require care. Based on healthy aging, the study was approved by the ethics committee under opinion number 5,497,833 and carried out with 13 elderly people who sought the Canaan Family Health Unit, located in the municipality of Trairi-Ce, from 04 to 07 July 2022. Its objective was to understand the discourses and practices involving healthy aging by the elderly. The study qualifies as qualitative and exploratory based on phenomenological data analysis. This study presented the results of healthy aging as synonymous with the absence of disease and the importance of the Family Health Strategy in the territory. Finally, it was noted that PHC can contribute positively to the promotion and monitoring of healthy aging regarding the quality of life of the elderly.